Robustness on Intuitionistic Fuzzy Connectives - Reiser, Renata Hax Sander; Bedregal, Benjamin Callejas (Trends in Computational and Applied Mathematics, 2014)
<!–StartFragment–>The main contribution of this paper is concerned with the robustness of intuitionistic fuzzy connectives in fuzzy reasoning. Starting with an evaluation of the sensitivity in n-order functions on the class of intuitionistic fuzzy sets, we apply the results in the intuitionistic (S,N)-implication class. The paper formally states that the robustness preserves the projection functions in such class.